Territories for Sale. The Catalogs of the Central American Countries for Universal Exhibitions at the End of the XIX Century - Cubero Barrantes, Guillermo (2020)
This article aims to presents the documents related to the assistance of Central American countries to the universal exhibitions of the 19th century, as documents reflecting the evident intention to attract the gaze of world political and economic powers towards the region, for which, their authors resorted to discursive reproduction and the mimicry of Western European culture. The cases of Costa Rica, Nicaragua, El Salvador and Guatemala are presented, each with the peculiarities that characterized them.